Treatment and Rehabilitation of Abused and Neglected Children an Inpatient Center Model - Fırat, Sunay; Çekin, Necmi; Gülmen, Mete Korkut; Avcı, Ayşe (The Bulletin of Legal Medicine, 2014)
Rehabilitation and treatment centers are organizations that provide services for children and adolescents, with the main goal being to implement a “mental health” treatment plan for the individuals under their care. These organizations, which provide a continuous 24-hour service, may differ from one another in terms of the specific programs and treatment methods they apply.The Oğuz Kağan Köksal Children and Youth Center was established in the Adana Province to provide for the treatment and rehabilitation of girls between the ages of 8 and 18 who have been subject to abuse or neglect, who suffer from alcohol/substance abuse, who are in need of treatment for mental problems and/or who live on the streets.A study was made of 72 girls who had been admitted to the institution for treatment and rehabilitation since 2004 with a history abuse and neglect. The girls were assessed with the Beck Depression Inventory (BDI), the State Anxiety Inventory (STAI-I), the Trait Anxiety Inventory (STAI-II) and the Maudsley Obsessive Compulsive Inventory (MOCI) upon being admitted to the institution and at the end of their stay (i.e. their discharge). The differences between the mean admission and discharge scores of the girls in the BDI, STAI-I, STAI-II and MOCI assessments was determined to be statistically significant (p
Keywords: residential treatment center; children; sexual abuse